Estudo da estrutura de custos e da economia de escala do setor de telecomunicações móveis do Brasil pós-privatizações - Vendruscolo, Maria Ivanice (Universidade do Vale do Rio do Sinos, 2007)
The telecommunication sector has been through significant structural transformations, technological innovations and changes in the regulatory processes, worldwide over the last decades. In Brazil, the mobile telephony, after-privatizations, followed the same trend, developing a complex oligopolistic structure. Initially, with the opening of the market, was adopted a structure in which the competition took place between A and B Bands operators. The second moment, with the achievement of the universalization targets, predictable by the new Brazilian telecommunications model, the competition between the operators was intensified, with the entrance of D and E Bands operators. Thus, with all the changes in the market structure of the Brazilian telephony sector, in the after-privatizations phase, this study aims to verify if the Brazilian operators of mobile telephony were usufructing economies of scale, through the analysis of the polynomial cost function and of cost curves. The research was of applied nature of
Keywords: Brasil; custos; privatizações; telecomunicações móveis; economia de escala; costs function; telecommunications; economies of scale; Ciências Sociais Aplicadas